PERSEPSI IBU TERHADAP PENGGUNAAN KONTRASEPSI SUNTIK - Roymond H. Simamora; Nugraha Wahyu C. (Fakultas Kesehatan Masyarakat, Universitas Jember, 2007)
Perception can be defined as a way of organism to give meaning. Perception called as comunication care, because if perception is inacurrate, it’s imposibble happened effective comunication. Perception can choose a message to diregard other message. Excelsior degree of quality of perception betwen individuals, its getting carier and they often comunicate increasingly and consequence tends increasingly forming group of cultur or group of identity. Injection contraception in Indonesia is one of popular contraception. Injection contraception applied is lomg acting progestin. As a result of this research is 53 responden (66,25%) mother has average of age 20-30 years. Respondens mayority using contraception of injection are graduate from high school (SMU). Having status as house wife are (68 (55 %). Having one child, the amount is (31 (40%), obtaining knowledge in the form of information from health officer are 49 (61%), injection contraception is applied based on safety and practical reason are 80 (100%), 62 (77,5%) wich has sigh of injection contraception making not regular menstruation. Sex activity becomes free are 80 (100%), it’s become safety device like condom and IUD aren’t required. Perception of responders to the advantage of the usage of injection contraception who tell good are 61 (76,3%). Man in general receives information from environment through some process, therefore in comprehending perception there must be a process which the information they got through the memory of a live organisme. Keywords : perceptions,mother, injection contraception